The Relationship between Interpersonal Relief, Life Expectancy and Religious Orientation with Public Health in Yasuj University Students - G ZadehBagheri; A Maredpour (Armaghane Danesh Bimonthly Journal, 2019)
Background & aim: Interpersonal life expectancy and forgiveness are two components of positive psychology that emphasize health promotion factors. In this regard, the relationship between religion and health and its interaction with interpersonal forgiveness and forgiveness in different cultures has been discussed. Therefore, this study aimed to determine the relationship between interpersonal happiness, life expectancy and religious orientation with general health among students.